Shroom3 facilitates optic fissure closure via tissue alignment and reestablishment of apical-basal polarity during epithelial fusion - Herstine, Jessica A; Mensh, Jordyn; Coffman, Electra; George, Stephanie M; Herman, Kenneth; Martin, Jessica B; Zatari, Ali; Chandler, Heather L; Kozmik, Zbynek; Drysdale, Thomas A; Bridgewater, Darren; Plageman, Timothy F (Developmental biology, 2025)
Optic cup morphogenesis is a complex process involving cellular behaviors such as epithelial folding, cell shape changes, proliferation, and tissue fusion. Disruptions to these processes can lead to an ocular coloboma, a congenital defect where the optic fissure fails to close. This study investigates the role of Shroom3, a protein implicated in epithelial morphogenesis, in mouse embryos during optic cup development. It was observed that Shroom3 is apically localized in the neural retina and retinal pigmented epithelium, and its deficiency leads to a both a conventional coloboma phenotype characterized by a gap in pigmented tissue as well as a unique type of coloboma where an ectopic ventral fold of neural tissue is present. Increased apical areas of both neural retina and retinal pigmented epithelial cells are present in the absence of Shroom3 leading to a greater apical surface area and disruption of optic fissure alignment. Neural retina specific gene ablation revealed that Shroom3 function in the RPE is likely sufficient to facilitate tissue alignment and permit fusion. However, the fusion process is ultimately disturbed due to a failure of the neural tissue to reestablish apical-basal polarity. Furthermore, it is demonstrated that Shroom3 deficiency also affects other epithelial fusion events in the embryo that rely on polarity reestablishment, such as lens vesicle separation, eyelid formation, and secondary palate closure. These findings highlight the importance of Shroom3 during optic cup morphogenesis, aid our understanding of optic fissure closure and coloboma formation, and implicates a role for Shroom3 in regulating apical-basal polarity.
Keywords: myši; morfogeneze; Retina; Morphogenesis; kolobom; zvířata; Mice; retinální pigmentový epitel; polarita buněk; retina; Retinal Pigment Epithelium; Cell Polarity; mikrofilamentové proteiny; Microfilament Proteins; Coloboma; Animals